2016
DOI: 10.1136/bmjopen-2016-013758
|View full text |Cite
|
Sign up to set email alerts
|

Association between organisational and workplace cultures, and patient outcomes: systematic review protocol

Abstract: IntroductionDespite widespread interest in the topic, no current synthesis of research is available analysing the linkages between organisational or workplace cultures on the one hand, and patient outcomes on the other. This protocol proposes a systematic review to analyse and synthesise the literature to date on this topic. The resulting review will discuss characteristics of included studies in terms of the type of healthcare settings researched, the measurements of organisational and workplace culture, pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(18 citation statements)
references
References 95 publications
(34 reference statements)
3
15
0
Order By: Relevance
“…In healthcare, a recent review across a variety of settings showed a consistent association between workplace culture and patient outcomes. However, most of the included studies were cross-sectional, using a wide range of different definitions and measurements of culture, environment and patient outcomes, and most studies were conducted in hospital settings 22. Safety culture in home healthcare has not yet been widely explored 23.…”
Section: Discussionmentioning
confidence: 99%
“…In healthcare, a recent review across a variety of settings showed a consistent association between workplace culture and patient outcomes. However, most of the included studies were cross-sectional, using a wide range of different definitions and measurements of culture, environment and patient outcomes, and most studies were conducted in hospital settings 22. Safety culture in home healthcare has not yet been widely explored 23.…”
Section: Discussionmentioning
confidence: 99%
“…In secondary care, culture is also a key determinant of behaviors. In a systematic review published in 2016, Braithwaite and colleagues identified a positive organizational culture (defined as values, norms, and beliefs) with positive patient outcomes [49]. The decline effect [50], where promising effects of an intervention are difficult to replicate in different settings, is a prime example of the influence of culture and context on behavioral outcomes.…”
Section: The Role Of Culture and Team Dynamics In Antibiotic Stewamentioning
confidence: 99%
“…However, the 17 studies were heterogeneous concerning methods and measures. Braithwaite et al (2017) indicated similar results in another review.…”
Section: Connection Between Patient Safety Culture and Patient Safetysupporting
confidence: 77%